Characteristics of patients with acute traumatic brain injury discharged against medical advice in a Level 1 urban trauma centre. (September 2014) - de Guise, Elaine; LeBlanc, Joanne; Dagher, Jehane; Tinawi, Simon; Lamoureux, Julie; Marcoux, Judith; Maleki, Mohammed; Feyz, Mitra
Abstract Primary objective: To predict which characteristics are associated with patients at risk of discharge against medical advice (AMA). Research design: Data were retrospectively collected on individuals (n = 5642) admitted to the Traumatic Brain Injury Program of the MUHC-MGH. Methods and procedures: Outcome measures used were length of stay (LOS), the Extended Glasgow Outcome Scale (GOSE) as well as the Functional Independence Measure (FIM®). Main outcomes: The overall rate of patients leaving AMA was 1.9% (n = 108). Age was negatively associated with AMA discharge (95% CI OR = [0.966;0.991]). Patients with a history of substance abuse were ∼2-times more likely to leave AMA than those not using substances before injury (95% CI OR = [1.172;3.314]) and the homeless were ∼3-times more likely to leave AMA compared to those who were not homeless (95% CI OR = [1.260;7.138]). Length of stay (LOS) was shorter for patients leaving AMA (p < 0.001) and they showed better outcome (GOSE: p < 0.001; FIM®: p = 0.032). Conclusions: Knowing the profile of patients with TBI leaving AMA hospitalized in an urban Level 1 Trauma centre will help in the development of effective strategies based on patient needs, values and pre-injury psychosocial situation to encourage them to complete their treatment course in hospital.